PENGARUH CORPORATE GOVERNANCE PERCEPTION INDEX, RISIKO, DAN KARAKTERISTIK PERUSAHAAN TERHADAP KINERJA KEUANGAN (STUDI EMPIRIS PERUSAHAAN GO PUBLIC DI CGPI) - Warenda, Okajaya Kusuma (Optimum: Jurnal Ekonomi dan Pembangunan, 2013)
This study examines the relationship between the corporate governance perception index, risk, and and firm characteristics that proxies by institutional ownership, growth opportunities (sales growth) and size on the firmâs financial performance measured using return on equity (ROE). The method to analys this study is regression . Data which used is the data from 2006-2012 for 86 companies was listed Indonesia Stock Exchange ( IDX ) and included in the ranking of The Indonesian Institute for Corporate Governance ( IICG ). The results indicates that corporate governance perception index, risk and growth opportunities (sales growth) have relationship with the firmâs financial performance. But, there is variable institusional ownership and size hasnât relationship with the firmâs performance.